EVALUATING DENTAL CARE QUALITY AND MANAGEMENT IN A MILITARY MEDICAL SETTING: THE CASE STUDY OF THE INSTITUTE OF AIR FORCE AND ANTIAIRCRAFT MEDICINE IN 2025. (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the quality and analyze influencing factors of the dental specialty clinic at the Institute of Air force and Antiaircraft medicine in 2025.Methods: A cross-sectional study design was employed, combining quantitative and qualitative methods. The research utilized the "Quality criteria for Odonto-Stomatology clinics" (version 2.0) consisting of 15 criteria to assess the current status. Data were collected through a retrospective review of professional records and in-depth interviews with 12 managers and medical staffs.Results: The average overall quality score of the clinic reached 3.5/5. Among the 15 criteria: 02 criteria achieved level 5 (13.33%), specifically radiation safety management and medical records; 05 criteria achieved level 4 (33.3%); 06 criteria achieved level 3 (40%) ; and 02 criteria reached level 2 (13.3%), which were patient safety and signage/advertising. No criteria were at level 1. Key influencing factors included: the financial autonomy mechanism, which increased proactivity but pressured revenue; an inconvenient examination process due to the clinic's isolated location on the 8th floor ; a lack of high-tech equipment (CAD-CAM, Laser) due to bidding obstacles ; and a shortage of high-level human resources caused by specific military duties resulting in local personnel disruptions.Recommendations: To enhance patient-centric care, capital investment in facility consolidation and the modernization of medical instrumentation must be prioritized. Furthermore, streamlining diagnostic protocols and accelerating the digital transformation of clinical management and communication systems are essential to improving operational efficiency..
Keywords: Clinic quality, Odonto-Stomatology, Institute of Air Force and Antiaircraft Medicine, Health management.